2007
DOI: 10.1016/j.nuclcard.2007.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of uptake and retention of F-18 BMS-747158-02 in cardiomyocytes: A novel PET myocardial imaging agent

Abstract: F-18 BMS-747158-02 is a novel positron emission tomography cardiac tracer targeting MC-I in cardiomyocytes with rapid uptake and slow washout. These characteristics allow fast and sustained accumulation in the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
118
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 22 publications
1
118
0
Order By: Relevance
“…The accumulation of 18 F-BMS was reported to depend on cellular MC-I activity, which is the first component of 4 electron transport complexes in the inner mitochondrial membrane (17,18). By an in vitro assay in a monolayer of neonatal rat cardiomyocytes, it was confirmed that 18 F-BMS uptake was inhibited by rotenone, a specific MC-I inhibitor (17).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The accumulation of 18 F-BMS was reported to depend on cellular MC-I activity, which is the first component of 4 electron transport complexes in the inner mitochondrial membrane (17,18). By an in vitro assay in a monolayer of neonatal rat cardiomyocytes, it was confirmed that 18 F-BMS uptake was inhibited by rotenone, a specific MC-I inhibitor (17).…”
Section: Discussionmentioning
confidence: 93%
“…The present study evaluated the capability of 18 F-BCPP-EF and 18 F-BCPP-BF (20) as PET probes for imaging the MC-I activity in the living rat brain in comparison with a previously reported probe 18 F-BMS (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations